Romania - Functional Review : Agriculture and Rural Development Administration - World Bank (Washington, DC, 2013)
This report presents the outcomes of the functional review of Romania's agricultural administration. Given the sectoral and territorial relevance of its regulatory domain, Romania s Agricultural and Rural Development Administration is a key administrative body undergoing this Functional Review. The review will examine whether the policy goals and objectives of the Ministry of Agriculture and Rural Development (MADR) and its agencies are clearly defined in measurable and achievable terms; whether the management systems, policies, staffing, and internal organizational structure are appropriate to meet objectives; and whether and to what extent factors external to the institutions impede the ability to meet objectives fully. The review analyzes factors promoting and/or limiting the efficiency and effectiveness of the agricultural and rural policy delivery in Romania. It aims at providing practical recommendations on: enhanced strategic coordination of policies and programs in the agricultural and rural policy domain; improved management and implementation of CAP support measures, to decrease risk of delayed payments to beneficiaries and low, ineffective and inefficient absorption of EU funds; realizing the full potential of MADR and its agencies through, for instance, better delineation of functions and better delegation of responsibilities within and among the relevant institutions; and approaches to improving the quality of public service delivery to beneficiaries of the Government's agricultural and rural programs. The review focuses on assessing both the current situation and future needs. It is broadly based on the following thematic areas: strategic framework, organizational structure and systems, budget and financial management, human resource management.